2020
DOI: 10.21203/rs.3.rs-15489/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing immune infiltration and the tumor microenvironment for the diagnosis and prognosis of sarcoma

Abstract: Background: Sarcomas, cancers originating from mesenchymal cells, are comprehensive tumors with poor prognoses, yet their tumorigenic mechanisms are largely unknown. In this study, we characterize infiltrating immune cells and analyze immune scores to identify the molecular mechanism of immunologic response to sarcomas.Method: The “CIBERSORT” algorithm was used to calculate the amount of L22 immune cell infiltration in sarcomas. Then, the “ESTIMATE” algorithm was used to assess the “Estimate,” “Immune,” and “S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Interestingly, Dhupkar et.al indicated that osteosarcoma lung metastases regression by anti-PD1 can be attributed to activated tumor macrophages M1 and reduced macrophages M2 [50]. Although there are few studies focused on macrophages M0, its relationship with other immune cells, such as CD8 T cells, has also been preliminarily reported [51]. Natural killer (NK) cells are important immune cells in the innate immune mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Dhupkar et.al indicated that osteosarcoma lung metastases regression by anti-PD1 can be attributed to activated tumor macrophages M1 and reduced macrophages M2 [50]. Although there are few studies focused on macrophages M0, its relationship with other immune cells, such as CD8 T cells, has also been preliminarily reported [51]. Natural killer (NK) cells are important immune cells in the innate immune mechanisms.…”
Section: Discussionmentioning
confidence: 99%